Secondary school entrance examinations in the Caribbean: Legacy, policy, and evidence within an era of seamless education - De Lisle, Jerome (School of Education, UWI, St. Augustine, 2012)
Secondary school entrance examinations remain an important feature of education systems within the Anglophone Caribbean. This is at a time when many high-performing school systems have either diversified traditional test-based placement mechanisms or completely postponed early selection and placement. In contrast, high-stakes secondary school selection/placement examinations have persisted in Caribbean nation states, albeit under the guise of reform. Paradoxically, in the postcolonial era of seamless education, some form of test-based selection and/or placement continues, with newly added roles, refined purposes, and exotic new names. These high-stakes systems compete strongly with formative classroom assessment and large-scale learning assessments used for monitoring student achievement. This paper argues that the persistence of test-based early selection in the Caribbean points to a widespread and implicit belief in the infallibility of test scores. This naïve perception among different publics has remained, even in the face of evidence from early sociological studies demonstrating inequalities on the examination. In the era of seamless education reform, there is need for an explicit measurement focus to better judge fairness, validity, and equity. Unless a fledgling Caribbean measurement community can head in the direction of collecting credible evidence, abuses and test score misuse will continue
Keywords: Entrance examinations; Secondary schools; Selection procedures; Testing; Caribbean